Pengaruh Penggunaan Smartphone Terhadap Prilaku Sosial Siswa Sekolah Menengah Umum di Kecamatan Sako Kota Palembang - Islamy, Diah Putri; Marpaung, Nora Noggety (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2022)
Smartphone is a telecommunication tool with current technology and continually improve the sophistication of features connected to web application media. Smartphone is also a tool that is inextricably linked to human life and activities, all activities are done by using internet, with modern technology in Smartphone. Especially in Covid 19 pandemic, when all activities of life are conducted online, including education, where face-to-face learning is substituted by online learning based on internet media. Smartphone with modern technology always provides comfort to the users, such as entertainment features and the ease of engaging with others through various social media, and the students do not forget to bring handphone wherever they are. Increasing Smartphone users among students, we need parental monitoring and guidance in the use of an effective smartphone to shape appropriate student attitude in a social context. This study used a quantitative approach with simple linear regression testing with SPSS 26 application. Data collection was done by observation, online questionnaire by using Google forms and offline observation through filling out questionnaire directly. The participants in this study were 95 senior high school students in Sako Palembang. The finding of this study showed that all of the question items x and y were valid and reliable. In final result, for variable x there was no effect for the usage of smartphone toward social behavior of senior high school student in Sako. This was based on process of calculating questionnaire in SPSS and showed t-value was smaller than t-table, it was 0.202.